Advances in Optical Fiber Sensing Using Gold/Silver Nanocomposites: A Review - Luthfiyyah, Siti Azimatul; Sunaryono, Sunaryono; Bakhtiar, Hazri; Hidayat, Arif; Hidayat, Nurul (Trends in Sciences, 2025)
The past 20 years have witnessed a marked increase in research focused on optical fiber sensors for their potential to detect changes due to physical and chemical properties. Various modifications on optical fibers have been explored to improve their sensing performance and application-specific suitability. One such approach involves the coating of optical fibers with plasmonic nanomaterials, enabling the activation of Localized Surface Plasmon Resonance (LSPR) effect. Among these, gold/silver nanocomposites (Au/Ag NCs) demonstrate strong LSPR effect that can enhance the sensitivity of optical fiber sensors. Diverse functionalization techniques have been developed to integrate these plasmonic nanomaterials effectively, while the structural configuration of the optical fiber is equally critical for attaining optimal sensing performance. This review highlights the role of Au/Ag NCs in advancing optical fiber capabilities, explores relevant fiber structures, examines the limitations and challenges, and discusses potential applications in healthcare, industry, and environmental monitoring. Finally, future research directions are proposed to guide further innovation in this rapidly evolving field. HIGHLIGHTS Gold/silver nanocomposites (Au/Ag NCs) enhance the performance of optical fiber sensors. The structure and type of optical fiber significantly influence the sensor performance. Au/Ag NCs coating methods on optical fiber include self-assembly monolayer, electroless plating, and photochemical deposition. Optical fiber sensors functionalized with Au/Ag NCs show great potential for applications in healthcare, industry, and environmental monitoring. GRAPHICAL ABSTRACT